FORENSIC ANALYSIS OF THE CONTENT OF AUDIO AND VIDEO RECORDINGS OBTAINED DURING INVESTIGATION: REVIEW OF CURRENT STATE AND FUTURE PROSPECTS - O. Gagina; V. Kuznetsov (Теория и практика судебной экспертизы)
The paper examines the current state of forensic analysis of audio and video materialsobtained during crime investigation. It outlines the methodological approach toaddressing the objectives of this type of forensic examination that has been developedby the Bryansk Forensic Science Laboratory.